The Perception of PAI Teachers on Character Education in PAI Learning - Hasanatul Maghfiroh (Journal of Practice Learning and Educational Development, 2025)
This study was conducted to find out how PAI teachers view character values in PAI learning, and how PAI teachers' readiness to implement character education in the classroom at UPT SDN 358 Gresik. This research used a qualitative approach. The type of research used is descriptive qualitative. Researchers used observation and interview methods. The result of this study is that PAI teachers at UPT SDN 358 Gresik have a good understanding of character education and implement it through exemplary, inspirational stories, and habits of worship. However, the main challenges faced are the limited time in the curriculum, the lack of support from parents, and the need to improve more innovative learning methods so that character values are taught more effectively. In conclusion, PAI teachers realize the importance of character education and have integrated it in learning. Despite facing obstacles, they still try to implement effective strategies. To increase its effectiveness, closer cooperation between schools and families and increased teacher competence in adaptive learning methods are needed